Public action and government accountability - Liu, Jianqiang (Chinese research perspectives. Environment, 2014)
This new volume of Chinese Research Perspectives on the Environment includes selected articles from the 2013 annual environmental report compiled by Friends of Nature, a leading environmental protection NGO in China, with contributions from academics, environmental protection activists, public service activists, and the media.